Obesity and risk of diseases associated with hallmarks of cellular ageing : a multicohort study - Kivimäki, Mika; Frank, Philipp; Pentti, Jaana; Xu, Xiaolin; Vahtera, Jussi; Ervasti, Jenni; Nyberg, Solja T; Lindbohm, Joni V; Jokela, Markus; Partridge, Linda (Elsevier, 2025)
Summary Background Ageing hallmarks, characterising features of cellular ageing, have a role in the pathophysiology of many age-related diseases. We examined whether obesity is associated with an increased risk of developing such hallmark-related diseases. Methods In this multicohort study, we included people aged 38–72 years with data on weight, height, and waist circumference measured during a clinical examination at baseline between March 13, 2006, and Oct 1, 2010, from the UK Biobank with follow-up until Nov 12, 2021. To test reproducibility of the findings (replication analysis), we used data from people aged 40 years or older included in the Finnish Public Sector study and the Finnish Health and Social Support study who responded to the study surveys, had data on BMI, and were successfully linked to electronic health records from national registers up to Dec 31, 2016. Obesity and clinical characteristics were assessed at baseline. Via linkage to national health records, participants were followed up for 83 diseases related to nine ageing hallmarks (genomic instability, telomere attrition, epigenetic alterations, loss of proteostasis, deregulated nutrient sensing, mitochondrial dysfunction, cellular senescence, stem cell exhaustion, and altered intercellular communication). Outcomes were the first instance of hallmark-related disease, in addition to co-occurrence of three or more hallmark-related diseases and mortality. Findings 496 530 adults (mean age 57·0 years [SD 8·1]) from the UK Biobank were included in the primary analysis, and 83 249 (mean age 48·2 years [6·4]) adults from the Finnish cohorts were included in the replication analysis. Median follow-up was 12·7 years (IQR 12·0–13·4) in the UK Biobank and 14·0 years (8·0–15·0) in the Finnish cohorts. After adjusting for demographic characteristics, lifestyle factors, and depression, UK Biobank participants with obesity (BMI ≥30·0 kg/m2) had a 1·40 (95% CI 1·38–1·41) times higher hazard ratio for the first hallmark-related disease than those with a healthy weight (BMI 18·5–24·9 kg/m2). The corresponding hazard ratios for three co-occurring diseases were 2·92 (95% CI 2·64–3·22) for deregulated nutrient sensing, 2·73 (2·46–3·02) for telomere attrition, 2·33 (2·10–2·60) for epigenetic alterations, 2·30 (2·14–2·48) for mitochondrial dysfunction, 2·23 (2·04–2·45) for stem cell exhaustion, 2·02 (1·89–2·16) for altered intercellular communication, 2·01 (1·89–2·15) for cellular senescence, 1·83 (1·67–2·00) for loss of proteostasis, and 1·39 (1·27–1·52) for genomic instability. These findings were replicated in the Finnish cohorts. In both studies, the associations between other risk factors (low education, unhealthy dietary factors [available only in the UK Biobank], smoking, high alcohol consumption, physical inactivity, and depression) and hallmark-related diseases were weaker than those with obesity. 45–60% of the excess mortality in people with obesity was attributable to hallmark-related diseases. Interpretation Obesity might have an important role in the development of diseases associated with cellular ageing. Tackling ageing mechanisms could potentially help to reduce the disease and mortality burden resulting from the obesity epidemic. Funding Wellcome Trust, UK Medical Research Council, US National Institute on Aging, Academy of Finland, and Finnish Foundation for Cardiovascular Research. Translations For the German and Finnish translations of the abstract see Supplementary Materials section.